Antibiotic Utilization in the Dental Clinic over 7 Years; Room for Improvement. (4th October 2017) - Collison, Maggie; Gupta, Kalpana; Koch, George; O'Brien, William; Smith, Donald; Strymish, Judith
Abstract: Background: At least 30% of antibiotic courses prescribed in the outpatient setting are unnecessary, meaning that no antibiotic is needed at all. Specialty areas such as dental clinic are a common place for antibiotic use and a potential for antibiotic overuse. The duration and indications for antibiotic use in dental clinics have not been clearly defined, except in the setting of endocarditis prophylaxis. Antibiotics are often used and sometimes indicated for endodontic, periodontal, implant and surgical procedures. Our goal was to measure antibiotic usage and duration in the dental clinic at a large VA hospital. Methods: Outpatient antibiotic prescriptions from 2010–2016 for VA Boston were extracted from the VA data warehouse. Prescriptions were classified by date, antibiotic, and duration. Dental clinic visits and associated CPT codes were extracted for visits within 7 days +/- prescription. Results: Of 119, 193 dental visits during the study period, 3.7% (4, 358) were associated with a unique antibiotic prescription. CPT diagnoses included periodontal (17.1%), endodontic (5.1%), surgical (36.5%) and implant (26.2%) procedures. The antibiotics prescribed included amoxicillin (62.0%), clindamycin (17.7%), penicillin (10.5%), macrolides (4.3%), augmentin (3.4%), and in less than 1% other classes including fluoroquinolones (0.2%). Mean days of antibiotics were 7.6 +/- SD 5.2 days (7.4 +/- SD 4.0 days for the above CPT codes). Duration did not vary by diagnostic code or by antibiotic class. There were no temporal trends over time. Conclusion: The majority of antibiotic use in dental clinic was for diagnostic codes that may warrant antibiotic use. The spectrum of activity of agents is in keeping with guidelines. However, the duration of antibiotics is longer than what might be anticipated for prophylaxis of dental procedures or treatment of dental infections. Limitations include lack of manual chart review to identify specific indication and potential for missing prescriptions by non-dental providers. Surveillance and stewardship activities can optimize antibiotic use in dental clinic. Disclosures: All authors: No reported disclosures.